New species of microcaddisflies from China (Trichoptera: Hydroptilidae) - Zhou, Lei; Yang, Lian-Fang; Morse, John C. (Zootaxa, 2016)
Five new species of hydroptilids in four genera are described from China, including three new species in Hydroptilinae: Agraylea dactylina n. sp., Allotrichia rhynchophyllum n. sp., and Microptila hamatilis n. sp.; and two new species in Stactobiinae: Stactobiella mutica n. sp. and Stactobiella parallelica n. sp. New records are given for Stactobiella biramosa Martynov 1929 and Pseudoxyethira thingana (Oláh) 1989. Genera Agraylea, Allotrichia, Stactobiella, and Microptila are new to Chinese fauna.